Conflict 101 : a manager's guide to resolving problems so everyone can get back to work - Shearouse, Susan H. (New York : American Management Association, 2011)
'Conflict 101' gives readers the tools they need to ensure not only that employees get back on track, but that disagreements breed positive results. Readers will learn how to: build trust; harness negative emotions; encourage apologies and forgiveness; use a solution-seeking approach; and, say what needs to be said. Incorporating anecdotes taken from the author's twenty years of experience as a conflict resolution professional, the book helps readers more deeply understand how conflict is created, how to respond to it, and how to manage it more effectively.
Includes bibliographical references and index.
Keywords: Conflict management; Interpersonal relations